Maximizing neuroprotection: where do we stand? - Kuffler DP (Dove Medical Press, 2012)
Damien P KufflerInstitute of Neurobiology, University of Puerto Rico, San Juan, Puerto RicoAbstract: Brain and spinal cord traumas include blunt and penetrating trauma, disease, and required surgery. Such traumas trigger events such as inflammation, infiltration of inflammatory and other cells, oxidative stress, acidification, excitotoxicity, ischemia, and the loss of calcium homeostasis, all of which cause neurotoxicity and neuron death. To prevent trauma-induced neurological deficits and death, each of the many neurotoxic events that occur in parallel or sequentially must be minimized or prevented. Although neuroprotective techniques have been developed that block single neurotoxic events, most provide only limited neuroprotection and are only applied singly. However, because many neurotoxicity triggers arise from common events, an approach for invoking more effective neuroprotection is to apply multiple neuroprotective methods simultaneously before the many neurotoxic triggers and cascades are initiated and become irreversible. This paper first discusses some triggers of neurotoxicity and neuroprotective mechanisms that block them, including hypothermia, alkalinization, and the administration of adenosine. It then examines how the simultaneous application of these techniques provides significantly greater neuroprotection than is provided by any technique alone. The paper also stresses the importance of determining whether the neuroprotection provided by these techniques can be further enhanced by combining them with additional techniques, such as the systemic administration of glucocorticoids. Finally, the paper stresses the absolute critical importance of applying these techniques within the “golden hour” following trauma, before the many neurotoxic events and cascades are manifest and before the neurotoxic cascades become irreversible.Keywords: adenosine, hypothermia, alkalinization, glucocorticoids